Relationships between dorsolateral prefrontal cortex metabolic change and cognitive impairment in first-episode neuroleptic-naive schizophrenia patients. Issue 25 (June 2017) - Huang, Man-Li; Khoh, Thong-Teck; Lu, Shao-Jia; Pan, Fen; Chen, Jin-Kai; Hu, Jian-Bo; Hu, Shao-Hua; Xu, Wei-Juan; Zhou, Wei-Hua; Wei, Ning; Qi, Hong-Li; Shang, De-Sheng; et al.
Abstract : Abstract: The present study aimed to explore the possible associations between the dorsolateral prefrontal cortex (DLPFC) metabolites and the cognitive function in first-episode schizophrenia (FES). This study included 58 patients with FES (29 males and 29 females; mean age, 22.66 ± 7.64 years) recruited from the First Affiliated Hospital, College of Medicine, Zhejiang University, and 43 locally recruited healthy controls (16 males and 27 females; mean age, 23.07 ± 7.49 years). The single-voxel proton magnetic resonance spectroscopy was used to measure the levels of N-acetylaspartate (NAA); complex of glutamate, glutamine, and γ-aminobutyric acid (Glx); choline-containing compounds; and myo-inositol in the DLPFC. The ratios of metabolites to creatine (Cr) were calculated. The cognitive function was assessed by Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery (MCCB). Correlation analysis was used to assess the relationships between the DLPFC metabolites and the cognitive function.Compared with the healthy controls, the patients with FES showed significantly reduced scores in each part of the MCCB, significantly reduced NAA/Cr, and significantly increased Glx/Cr in the left DLPFC. Poor performance in verbal learning and visual learning was correlated to the reduced NAA/Cr ratio in the left DLPFC. These findings suggest that a lower NAA/Cr ratio in the left DLPFC is associated with the cognitive deficits in patients with FES, and may be an early biochemical marker for the cognitive impairment in schizophrenia.